2016
DOI: 10.1093/ehjqcco/qcw018
|View full text |Cite
|
Sign up to set email alerts
|

The role of mHealth for improving medication adherence in patients with cardiovascular disease: a systematic review

Abstract: Cardiovascular disease is a leading cause of morbidity and mortality worldwide, and a key barrier to improved outcomes is medication non-adherence. The aim of this study is to review the role of mobile health (mHealth) tools for improving medication adherence in patients with cardiovascular disease. We performed a systematic search for randomized controlled trials that primarily investigated mHealth tools for improving adherence to cardiovascular disease medications in patients with hypertension, coronary arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
112
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(140 citation statements)
references
References 35 publications
4
112
0
5
Order By: Relevance
“…Figure 2 shows the services that can be delivered by mHealth. 545 | P a g e www.ijacsa.thesai.org There are several research have been done to investigate the potential use of mHealth for Cardiovascular disease management [3,4,5,7,8,9,10,11,12,13]. The details explanations for those related research are as follows:…”
Section: Mobile Health Application For Cardiovascularmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 2 shows the services that can be delivered by mHealth. 545 | P a g e www.ijacsa.thesai.org There are several research have been done to investigate the potential use of mHealth for Cardiovascular disease management [3,4,5,7,8,9,10,11,12,13]. The details explanations for those related research are as follows:…”
Section: Mobile Health Application For Cardiovascularmentioning
confidence: 99%
“… Gandapur et al [5] explain that mHealth can be used to improve medication adherence for cardiovascular disease. The aim of their research is to assess mHealth as a tool to provide better medication obedience for cardiovascular disease patients, especially patients with hypertension, coronary artery disease, heart failure, peripheral arterial disease, and stroke.…”
Section: Mobile Health Application For Cardiovascularmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that mobile phone-based approaches are efficacious, user-friendly means for communicating with participants, providing instructions, and modifying behaviors [44]. In addition to their practical utility, mHealth technology may also be leveraged to promote health equity.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…The device also can only record the prescription intake and does not provide any reminder or alert for missing dosage. It is necessary to alert the patients to take the missing doses using device such as CompuMed [5] and mHealth [6].…”
Section: Introductionmentioning
confidence: 99%